Thoracic reconstruction of exposed lung by contralateral pectoralis major muscle flap - Kumar, Ravindra; Mishra, Brijesh; Upadhyaya, Divya Narain; Sharma, Navneet (Indian Journal of Case Reports, 2020)
Chest wall defects are defined as defects with variable loss of skin, muscles, and rib cage with exposed pleura or lung. The exposed lung is a life-threatening emergency and requires urgent intervention to restore airtight closure. We use contralateral pectoralis major muscle turnover flap to obliterate dead space and airtight closure for full thickness right-sided chest wall injury with exposed lungs.